Sofosbuvir-Based Therapies for Patients with Hepatitis C Virus Infection: Real-World Experience in China - Chengguang Hu; Guosheng Yuan; Junwei Liu; Huaping Huang; Yanyu Ren; Yinping Li; Xuefu Chen; Wei Li; Tao Wu; Hong Deng; Yanzhong Peng; Yong-Yuan Zhang; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. There is scarcity of data in literature regarding the treatment response to sofosbuvir- (SOF-) based therapies in Chinese patients with chronic Hepatitis C Virus (HCV) infection. The aim of this study was to evaluate the efficacy and safety of SOF-based regimens for chronic hepatitis C (CHC) patients without cirrhosis in a real-world setting in mainland China. Methods. A total of 226 patients receiving SOF plus daclatasvir (DCV), ledipasvir (LDV), or velpatasvir (VEL) were enrolled from December 2014 to June 2017. The primary observation point was the percentage of patients with a sustained virologic response (SVR) at posttreatment week 12 (SVR12), and all adverse events were monitored during treatment and follow-up period. Results. The overall SVR12 rate was 96% (216/226), and individual SVR12 ranged from 93% to 100% in different treatment groups. No significant differences of efficacy were detected between genotypes 1b and 6a (98% for GT 1b versus 100% for GT 6a, P=0.322). Comparing the high success rates in GT 1b and 6a patients, SVR12 was relatively low in GT 3a and 3b patients. A significant difference in efficacy was observed between GT 3 and not GT 3 patients (77% versus 98%, respectively, P<0.001). No significant differences in efficacy were detected among different regimens (93% versus 97% versus 100%, respectively, P=0.153), gender (95% for male versus 96% for female, P=0.655), or baseline HCV RNA lever (96% versus 95%, respectively, P=0.614). Similar SVR rates were also obtained in naïve and previously treated patients (98% versus 93%, respectively, P=0.100). Conclusions. NS5B polymerase inhibitor SOF plus one of the NS5A inhibitors, such as DCV, LDV, or VEL for 12 weeks was associated with high SVR12 rates and well tolerated in HCV-infected patients without cirrhosis. Moreover, patients with DAAs failure should be retreated with more effective regimens like SOF/VEL.